2021
DOI: 10.1007/s40121-021-00511-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Efficacy and Safety of PEGylated Interferon-α2b Treatment in Inactive Hepatitis B Surface Antigen Carriers

Abstract: Introduction: Hepatitis B virus (HBV) infection is associated with the onset of several major liver diseases. Inactive hepatitis B surface antigen (HBsAg) carriers (IHCs) may be successfully treated with PEGylated interferon-a2b (PEG-IFNa2b)-based antiviral therapy; however, studies on this treatment have been insufficient. In this study, we evaluated the efficacy and safety of PEG-IFNa2b treatment in IHCs. Methods: Nineteen IHCs were treated with subcutaneous PEG-IFNa2b (180 lg/week) for 48 weeks (treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…A recently published European study showed that 24-week HBsAg decline during PegIFNα-based treatment was superior to 12-week HBsAg decline for predicting subsequent HBsAg loss [23], which was confirmed in the present study. In addition, this study confirmed the conclusion that the lower the baseline HBsAg level, the higher the functional cure rate, as reported previously [12,13,24–27].…”
Section: Discussionsupporting
confidence: 92%
“…A recently published European study showed that 24-week HBsAg decline during PegIFNα-based treatment was superior to 12-week HBsAg decline for predicting subsequent HBsAg loss [23], which was confirmed in the present study. In addition, this study confirmed the conclusion that the lower the baseline HBsAg level, the higher the functional cure rate, as reported previously [12,13,24–27].…”
Section: Discussionsupporting
confidence: 92%
“…After final screening, 12 articles were excluded, i.e., one article with a small sample size, three articles with incomplete outcome data, two articles with the same cohort, and six articles with baseline HBsAg <1500 IU/mL but not in compliance with one or more IHC criteria. Finally, a total of 11 articles were included in this meta-analysis (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Resultsmentioning
confidence: 99%
“…All 11 studies were conducted in Asia, including 10 in China and one in Singapore ( 13 ). Seven articles were published in English ( 11 15 , 20 , 21 ) and four in Chinese ( 16 – 19 ). The baseline HBsAg levels were <20 IU/mL in two studies ( 14 , 16 ), <100 IU/mL in one study ( 12 ), <1000 IU/mL in six studies ( 11 , 13 , 17 , 18 , 20 , 21 ), and <1500 IU/mL in two studies ( 15 , 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also the first cytokines used in therapy ( 33 ). IFNs are used to treat autoimmune diseases including multiple sclerosis ( 34 ), tumors such as lymphoma ( 35 ), infectious diseases such as disseminated nocardiosis ( 36 ), and hepatitis C ( 37 ). Recently, it is even considered as a potential therapeutic target for COVID-19.…”
Section: Ifns and Their Absmentioning
confidence: 99%